Peronism as a model of social and political development: The modern Argentinian myth - Krstić Zoran (Međunarodni Problemi, 2014)
The subject of the analysis in this paper is the study of the emergence and evolution of the phenomenon of Peronism as the most important political movement and ideology in Argentina and perhaps in Latin America throughout the 20th century. The basic aim of this paper is to present Peronism as a political movement and model of development which emerged during the rule of Juan Domingo Peron in the mid-20th century. This movement continued to exist and last after Peron’s demission from the political scene. In recent history Peronism became something more significant than a political movement or a social development model. Because of that, Peronism can be characterized as a myth. Nowadays, Perosnism is one of the crucial factors in the socio-economic and cultural development in Argentina. The focus of research in this paper is on the presentation and explication of the notions/topics concerning Peron, his movement and rule. These ones are populism, presidentialism and personalisation of power. Also, this paper will analyse the conditions, facts and circumstances under which Peronism emerged and survived in spite of many critics and disputes in the scientific literature as well in the Argentinian politics and society.